Green innovations in urban landscape: opportunities to use Slovakia’s experience - Maksymenko , N. V.; Bihuňová, M. (Man and Environment. Issues of Neoecology, 2024)
Purpose. To analyze the results of an internship at the Slovak Agricultural University in Nitra, which was aimed at studying the possibility of introducing green industrial innovations into urban landscapes under the project of the International Visegrad Fund "Green Innovations in Urban Landscape Ecology". Results. The experience of creating an interactive living laboratory of green innovations "ReImaGIne Living Lab" was studied and the possibilities of implementing this methodology in Kharkiv were analyzed. The scenarios of transformation of open space into a sustainable multifunctional city park are investigated. The project on the use of green and blue infrastructure elements in the construction of the Nivy bus station in Bratislava is analyzed and the availability of green infrastructure elements in Slovak cities is assessed. Conclusion. In order to implement green innovations in Ukraine, which are widely represented in Slovakia, it is necessary to modernize the training of specialists through new teaching models, as well as the introduction of the principles of sustainable development in the educational procesS.